Eyes of Aniso-Axial Length Individuals Share Generally Similar Corneal Biometrics with Normal Eyes in Cataract Population - Min Zhang; Tianhui Chen; Michael Deng; Jiahui Chen; Qinghe Jing; Yongxiang Jiang (Journal of Ophthalmology)
Aims. To determine the characteristics of corneal biometrics in eyes from aniso-axial length cataract patients compared with eyes from non-aniso-axial length individuals. Methods. This is a retrospective case series. Cataract patients with preoperative binocular measurements were recruited. A binocular axial difference of ≥1 mm was considered to indicate aniso-axial length. The anterior segmental biometrics were measured using Pentacam HR (Oculus, Wetzlar, Germany) and IOLMaster 500 (Carl Zeiss Meditec, Jena, Germany). Comparisons of biometrics were made among 4 eye conditions: the longer eyes from aniso-axial length patients, the shorter eyes from aniso-axial length patients, the longer eyes from non-aniso-axial length patients, and the shorter eyes from non-aniso-axial length patients. The aniso-axial length eyes were also stratified into 8 subgroups with axial length (AL) increments of 1 mm, and the biometrics of the subgroups were compared. Results. There was smaller anterior corneal astigmatism in the shorter aniso-axial length group than those in the longer aniso-axial length group (1.01 ± 0.70 D vs 1.12 ± 0.76 D, P=0.031). The longer aniso-axial length eyes had greater anterior corneal steep curvature (44.13 ± 1.69 D vs 43.87 ± 1.69 D, P=0.009) and anterior corneal astigmatism (1.12 ± 0.76 D vs 1.02 ± 0.69 D, P=0.023) compared with longer non-aniso-axial length subjects. Other corneal biometrics were similar between the aniso-axial length eyes and the non-aniso-axial length eyes. In the longer aniso-axial length group, the posterior corneal aberrations of eyes in the ≥5 mm subgroups were greater than those in the <5 mm subgroups (0.879 ± 0.183 μm vs 0.768 ± 0.178 μm for total aberrations, P<0.001; 0.228 ± 0.086 μm vs 0.196 ± 0.043 μm for high-order aberrations, P=0.036; 0.847 ± 0.173 μm vs 0.741 ± 0.179 μm for low-order aberrations, P=0.001). Conclusion. Eyes of aniso-axial length individuals share generally similar corneal biometrics with normal eyes in cataract population. Anterior corneal astigmatism of the longer eyes from the aniso-axial length cataract patients was higher than that of the longer eyes from the non-aniso-axial length individuals. Total posterior corneal aberrations of the longer aniso-axial length eyes increased when the binocular axial difference was over 5 mm.